Personal Preference of Mode of Delivery. What do Urogynaecologists choose? Preliminary Results of the DECISION Study - Bihler, Julia; Tunn, Ralf; Reisenauer, Christl; Pauluschke-Fröhlich, Jan; Wagner, Philipp; Abele, Harald; Rall, Katharina K.; Naumann, Gert; Wallwiener, Markus; Brucker, Sara Y.; Hübner, Markus (Geburtshilfe und Frauenheilkunde, 2017)
Introduction Currently, almost every third child in Germany is delivered by caesarean section. Apart from straightforward and clear indications for caesarean section which account for approx. 10%, the large proportion of relative indications in particular needs to be critically reviewed if the current C-section rate is to be effectively lowered. It is more than doubtful, however, whether this can be a realistic goal in Germany, especially in the context of international developments. All studies on this topic demonstrate that the personal attitude of the obstetric team has a considerable influence on the pregnant womanʼs personally preferred mode of delivery. Therefore, in the first part of the DECISION study, the personal preferences of urogynaecologists were evaluated regarding the best suitable mode of delivery.Material and Methods All 432 delegates at the 9th German Urogynaecology Congress in Stuttgart in April 2017 were invited to participate in an online questionnaire study. The questionnaire was developed especially for this study.Results Of the 432 registered delegates, 189 (43.8%) participated in the survey. 84.7% (n = 160) of the study participants would prefer a vaginal delivery, in an otherwise uncomplicated pregnancy. Only 12.2% (n = 23) opted for an elective caesarean section. The main reasons stated for this decision were concerns about incontinence (87.5%) and pelvic floor trauma (79.2%). Amongst the study participants, 83.6% would like to be part of a risk stratification system presented in the questionnaire which, with the aid of specific parameters, is intended to allow early identification of a population with a high risk of developing pelvic floor disorders. There was also great interest in postpartum pelvic floor recovery (97.8%) and an associated optional pessary therapy (64.4%). The type of delivery already experienced (vaginal delivery vs. primary caesarean section) and parity also reveals to have a significant influence on the personal preferred mode of delivery as well.Conclusions Urogynaecologists prefer vaginal delivery for themselves. There is a great interest to participate in a risk stratification process in order to approach childbirth in an individualized and risk-adapted manner.
Keywords: mode of delivery; elective caesarean section; risk stratification; postpartum recovery; pessary therapy